Analysis of the relationship between the ENSO phenomenon, Net Primary Productivity and catches of yellowfin tuna in Sibolga Waters, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Fadhilah A, Leidonald R, Susetya IE, Dewinta AF. 2022. Analysis of the relationship between the ENSO phenomenon, Net Primary Productivity and catches of yellowfin tuna in Sibolga Waters, Indonesia. Biodiversitas 23: 4440-4447. The eastern Indian Ocean includes the western seas off of North Sumatra. They have a high potential for catching fish, which is a measure of their degree of primary production. Numerous factors, including oceanic conditions and the El Niño Southern Oscillation (ENSO) phenomena, frequently have an impact on its potential. Additionally, ENSO has an influence on the availability of nutrients that generate chlorophyll, a component of primary production, as well as water mass. It is also responsible for anomalies of sea surface temperature (SST) that occur in the Pacific Ocean. Therefore, this study aims to determine the effect of the ENSO phenomenon on primary productivity as well as the abundance of yellowfin tuna (Thunnus albacares) in the western waters of North Sumatra. Data were obtained from the Aqua MODIS level 3 satellite for analysis of net primary productivity (NPP) using various parameters, namely Vertically Generalized Production Model (VGPM), Ocean Niño Index (ONI), yellowfin tuna catch, winds from ERDDAP, and currents from AVISO. Its relationship with the abundance of yellowfin tuna, and ENSO was then determined using the Pearson correlation. The VGPM calculation showed that NPP for 2016-2020 ranged from 275.169 mgC/m2 to 994.898 mgC/m2. The study also revealed that the ENSO phenomenon has a weak relationship with primary productivity and the abundance of yellowfin tuna with correlation values of 0.262 and -0.191, respectively.